A Critique of Anti-heterosexist Curriculum and Student Consent at the Toronto District School Board - Matrim, Jair (Paideusis, 2014)
Efforts to embed anti-heterosexist curriculum at the Toronto District School Board (TDSB) can become confused and contradictory because of the persistent subjection of the student to the curriculum, and by maintaining sex as a subject of danger and prohibition. Examples from the new TDSB anti-discrimination curriculum resource that were perceived as politically controversial in 2011 are briefly assessed with the popular queer(ed) theories of Foucault (1978/1990), Butler (1990; 1993), and Rubin (1984/1993). Deleuze's (1988) interpretation of Spinoza’s work is also plumbed to explain the consequences of heterosexist discourse in schools. The Deleuzian-Spinozan example of the caricatures of the “moralist trinity” shows that heterosexist discourses promote the production of “sad passions” throughout social relationships by creating “sad” characters within each individual. Finally, anti-heterosexist action in schools is described as modelling consent in curriculum and exposing relationships of subjection.